The versatility of terraced housing in Iranian vernacular architecture located in steep regions - Reza, Ehsan; Dinçyürek, Özgür (Open House International Association P.O. Box 74, Gateshead, Tyne and Wear, 2017)
This study explores the characteristics of a particular vernacular architecture, which is known as terraced housing. Terraced housing can be found in many different mountainous parts of the world such as the mountainous regions of Bahrain, Afghanistan, Pakistan, Greece, Italy and Japan, which have different environmental and cultural characteristics, and which were built in response to human needs according to the particular topographical conditions. Amongst the examples mentioned, Iranian terraced housing remains distinctive with its local richness and variation, constructed and designed according to the topography of the region. Accordingly the general overview of Iranian vernacular architecture and form is examined by focusing on the environmental factors of two specific Iranian villages. The identification of these villages is evaluated according to the topography, climate, urban pattern and spatial organization of Iranian terraced settlements. As a consequence, the analysis of case studies and data processing will enable decision makers, planners, architects and designers to become more aware of the existing architectural building tradition. The contemporary housing design problems can be solved by employing an appropriate method of design and building construction with reference to the present vernacular housing stock.
Keywords: Iranian; Steep topography; Terraced housing; Vernacular architecture